Limiting the Surveillance Period to 90 Days Misses a Large Portion of Infections in the First Year After Total Hip and Knee Arthroplasty - Stefano Muscatelli, MD; Huiyong Zheng, PhD; Aditya Muralidharan, MD; Viktor Tollemar, MD; Brian R. Hallstrom, MD (Arthroplasty Today, 2022)
Background: In 2013, the Centers for Disease Control and Prevention reduced the periprosthetic joint infection (PJI) surveillance period from 1 year to 90 days for total hip (THA) and knee arthroplasty (TKA). Our aim was to determine how the reduced surveillance window impacts capture of PJIs. Material and methods: Primary and revision THA and TKA cases were retrospectively identified in a statewide registry from October 1, 2015, to September 30, 2018. Infections were defined using the Periprosthetic Joint/Wound Infection measure (Centers for Medicare and Medicaid Services). We compared the cumulative incidence of infected primary and revision THA (pTHA/rTHA) and TKA (pTKA/rTKA) at 0-90 days and 91-365 days postoperatively. Results: A total of 136,491 patients were included, 59.59% female, mean age 65.8 years, and mean body mass index 32.3 kg/m2. The overall rate of PJI diagnosed by 1 year was 1.33%. The percent of infections diagnosed between 0-90 days and 91-365 days were pTHA 76.78% and 23.22%, rTHA 74.12% and 25.88%, pTKA 57.67% and 42.33%, and rTKA 53.78% and 46.22%, respectively. More infections were diagnosed after 90 days in pTKA than in pTHA and in rTKA than in rTHA (P < .0001). There was a higher risk of infection throughout the year when comparing rTKA to rTHA (P = .0374) but not when comparing pTKA to pTHA (P = .0518). Conclusion: A substantial portion of infections are missed by the 90-day surveillance period. More infections are missed after TKA than after THA. Extension of the surveillance period would allow for identification of opportunities for quality improvement.